Revisiting the δ Scuti star FG Virginis using Kepler K2 and TESS data - Guzik, Joyce A.; Jackiewicz, Jason; Hedlund, Anne M. (Frontiers in Astronomy and Space Sciences, 2022)
FG Virginis is a delta Scuti variable star that was the target of ground-based multisite photometric campaigns from 1992 to 2004. Over 75 pulsation frequencies were detected (Breger et al. 2005), more than for any other delta Scuti star before the era of space photometry. FG Vir was observed for 52 days in 30-minute cadence photometry by the NASA Kepler spacecraft K2 mission in 2016, and for 23 days in 2-minute cadence photometry by the NASA TESS spacecraft in 2021. We present light curves and amplitude spectra obtained from these space missions. We find around 30 significant frequencies in the K2 data, and over 100 significant frequencies in the TESS data. There is good correspondence between the first 10 or so highest-amplitude modes found in the K2 and TESS data and those found from the ground-based multisite data, although the amplitude order is slightly different, indicating some stability in mode frequencies and amplitudes spanning 20 years. However, the 9th highest-amplitude mode of Breger et al. has moved down in amplitude rank, while the 35th highest-amplitude mode has moved up to near the top ten as seen in both the K2 and TESS data. We find several low frequencies between 0.3 and 3 cycles per day in the TESS data that were not detected using the ground-based data. If low-frequency pulsations are confirmed, FG Vir would be classified as a delta Sct/gamma Dor hybrid variable. We also review stellar model results and challenges for asteroseismology for this well-studied delta Sct star.